Transcriptome profiles of soybean leaves and roots in response to zinc deficiency. Issue 3 (9th February 2019) - Zeng, Houqing; Zhang, Xin; Ding, Ming; Zhang, Xiajun; Zhu, Yiyong
Abstract : Zinc (Zn) deficiency is a widespread agricultural problem in arable soils of the whole world. However, the molecular mechanisms underlying Zn‐deficiency response are largely unknown. Here, we analyzed the transcriptomic profilings of soybean leaves and roots in response to Zn deficiency through Illumina's high‐throughput RNA sequencing in order to understand the molecular basis of Zn‐deficiency response in the plants. A total of 614 and 1011 gene loci were found to be differentially expressed in leaves and roots, respectively, and 88 loci were commonly found in both leaves and roots. Twelve differentially expressed genes (DEGs) were randomly selected for validation by quantitative reverse transcription polymerase chain reaction, and their fold changes were similar to those of RNA‐seq. Gene ontology enrichment analysis showed that ion transport, nicotianamine (NA) biosynthetic process and queuosine biosynthetic process were enriched in the upregulated genes, while oxidation–reduction process and defense response were enriched in the downregulated genes. Among the DEGs, 20 DEGs are potentially involved in Zn homeostasis, including seven ZRT, IRT‐related protein ( ZIP ) transporter genes, three NA synthase genes, and seven metallothionein genes; 40 DEGs are possibly involved in diverse hormonal signals such as auxin, cytokinin, ethylene and gibberellin; nine DEGs are putatively involved in calcium signaling; 85 DEGs are putative transcription factor genes. Nine DEGs were found to contain zinc‐deficiency‐response element in their promoter regions. These results could provide comprehensive insights into the soybean response to Zn deficiency and will be helpful for further elucidation of the molecular mechanisms of Zn‐deficiency response and Zn‐deficiency tolerance in plants.